Reduction of environmental pollution by using RTK-navigation in - Kelc, Damijan; Stajnko, Denis; Berk, Peter; Rakun, Jurij; Vindiš, Peter; Lakota, Miran (International Journal of Agricultural and Biological Engineering, 2019)
The concept of precision farming is wide, and it represents the efficiency which is achieved with the help of precision. For the navigation of field machines, the RTK (Real Time Kinematic) navigation is needed. In order to verify the positive effects in practice, RTK navigation system equipped with Fentd 828 was applied to test the width of overlap, and fuel and time that could be saved compared with manual driving. The experiment was conducted on two areas of land size of 172 m × 58 m with two working machines width 3 m and 6 m. Results indicated that 15.7% of the time and 8.66% of the fuel were saved on a working machine of 3 meters width, and 12.6% of the time and 8.28% of the fuel were saved on a working machine of 6 m width. The width of the overlap represent 10% of the working width of the machine, and with the method of turning, which RTK navigation allows, additional time was saved. Ecological footprint, CO2 emissions and global warming potential (GWP) was estimated under different guiding systems. The largest footprint was related to manual tillage with 3 m width working machine, while estimation on CO2 (kg) emissions and GWP obtained the same result. The use of precision agriculture technologies allows better planning and analyzing of working procedures. The air, water and soil pollution are less intensive. Keywords: precision farming, RTK technology, ecological footprint, environmental pollution, tillage DOI: 10.25165/j.ijabe.20191205.4932 Citation: Kelc D, Stajnko D, Berk P, Rakun J, Vindiš P, Lakota M. Reduction of environmental pollution by using RTK-navigation in soil cultivation. Int J Agric & Biol Eng, 2019; 12(5): 173–178.